PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN KETERAMPILAN SOSIAL SISWA KELAS V SDN TANGKIL 01 WLINGI - Sari Dewi; Sumarmi Sumarmi; Ach. Amirudin (Graduate School of Universitas Negeri Malang, 2016)
This study aims to apply the PBL learning model to the activity and social skills of students. Subjects were students of fifth class in SDN (elemantary school) Tangkil 01 Wlingi academic years 2015/2016. This type of research is classroom action research. Collecting data using observation sheet. Data were analyzed using descriptive analysis. The results of the study that (1) PBL learning model can improve students' activity, with enhancement an average score of student activity from the first cycle to the second cycle 26.67 and (2) PBL learning model can improve the social skills of students, with enhancement an average score social skills of students from the first cycle to the second cycle of 39.26. The suggestion that the need to regulate the allocation of time on the stage of discussions and presentations.Penelitian ini bertujuan menerapkan model pembelajaran PBL terhadap keaktifan dan keterampilan sosial siswa. Subyek penelitian adalah siswa kelas V SDN Tangkil 01 Wlingi TA. 2015/2016. Jenis penelitian adalah penelitian tindakan kelas. Pengumpulan data menggunakan lembar observasi. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian, yaitu (1) model pembelajaran PBL dapat meningkatkan keaktifan siswa, dengan peningkatan skor rata-rata dari siklus I ke siklus II sebesar 26,67 dan (2) model pembelajaran PBL dapat meningkatkan keterampilan sosial siswa, dengan peningkatan skor rata-rata dari siklus I ke siklus II sebesar 39,26. Saran yang diberikan, yaitu perlu mengatur alokasi waktu pada tahapan diskusi dan presentasi.